Analisis Pengelolaan Obat Di Rumah Sakit Umum Anuta Pura Palu - Tien Wahyu Handayani; Asiah Hamzah; Saifuddin Saifuddin (LP3M Universitas Muhammadiyah Makassar)
The aim of the research is to analyze the process of drug management involving planning, supply, receipt, storage, distribution, recording of reporting, evaluation and drug removal in Regional Public Hospital Anutapura in Palu city. The results reveal that planning process is already in accordance with hospitals’ procedure operational standard with consumption method. The selection of the types of drug is not always appropriate because the case of diseases and patients’visit could not be predicted. Supply process refers to President Regulation Number 95 The year 2007 with direct purchase method. The unsuitability of acceptance is caused by unavailability of drugs in distributor level. Storage process is not in line with rules because the condition of storage is not qualified. The distribution process is line with a prescription system and room supply. Drug distribution based on prescription is not completely served because the availability of prescription formulation of drugs is not appropriate. Evaluation is not maximal and one of them is name stock done at the end of each year.